Pengelolaan Arsip Dinamis Inaktif di Lembaga Pendidikan Sekolah Menengah Kejuruan - Aria Mulyapradana; Ary Dwi Anjarini; Nanang Hermanto (Universitas Bina Sarana Informatika, 2021)
This study aims to find out what are the obstacles faced in managing archives in the administration section and the things that are done to optimize the management of inactive dynamic records. The method in this research is qualitative and data collection is obtained by observation, interview, and documentation methods. The results of this study indicate that the management of archives in the Administration of Vocational High Schools has not been carried out optimally because there are still obstacles such as manual information systems in managing archives, uncluttered workspace layout, limited archive storage space, limitation of supporting infrastructure for archiving. and limited human resources in managing records. Based on the results of these studies, the archive management system is still not optimal and needs to be paid attention by the leadership so that archive management can be well organized and effective.